hubungan antara persepsi anak terhadap perhatian orang tua dan tanggung jawab dengan penyesuaian diri - Sucipto, Muhammad Hardwin Adi; Purwati, Purwati; Kurniati, Astiwi (Universitas Muhammadiyah Magelang, 2021)
This study aims to examine the relationship between children's perceptions of parental attention and responsibility with adjustment in the Rohmatullah Cokro Islamic Boarding School environment. This research is a type of correlational research that aims to determine the relationship between children's perceptions of parental attention and responsibility in the adjustment of students at the Rohmatullah Cokro Islamic Boarding School. This research was conducted on 30 students of class VIII. The results showed that the child's perception of parental attention and responsibility with adjustment had an effect. This is evidenced by the results of the H1 test using multiple linear, saying the significant value for the effect of children's perceptions on parents' attention (X1) with adjustment (Y) is 0.040 <0.05 and the value of Tcount is 2.159>Ttable 2.051831, the test results H2 using multiple linear says the significant value for the influence of responsibility (X2) with self-adjustment (Y) is 0.032 <0.05 and the Tcount is 2.262>Ttable 2.051831, the results of the H3 test with a significance value for the effect of children's perceptions on parental attention (X1) and responsibility (X2) simultaneously with self-adjustment (Y) is 0.000 <0.05 and Fcount 10.892 <Ftable 3.34, and determination test is 0.668 / 66.8%. It can be concluded that the relationship between children's perceptions of parental attention and responsibility with adjustment is significantly related.